Analisis Kepastian Hukum Terkait Pencegahan Tindak Pidana Penipuan Online Berdasarkan Undang-Undang ITE: Penelitian - Elshavira Suryaning Tyas; Adhining Prabawati Rahmahani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The digital revolution has triggered a surge in cybercrime, particularly online fraud through phishing schemes that significantly detriment banking customers. The primary objective of this study is to examine the regulation and implementation of online fraud prevention provisions under the ITE Law, as well as to analyze the legal certainty regarding these preventive measures. The research methodology employed is normative legal research with a statute approach, utilizing data collected through literature studies. The results indicate that while preventive regulations are established under Article 28 paragraph (1) and Article 40 paragraphs (2a) and (2b) of the ITE Law, their practical implementation remains reactive and ineffective. The analysis of legal certainty reveals a discrepancy between das sollen and das sein, caused by the delayed response of Electronic System Providers (PSE), the absence of a Rapid Response Time Standard (RRTS), and violations of the bank's principle of professionalism in handling emergency customer complaints. In conclusion, legal certainty can be achieved by synchronizing normative clarity, professional and rapid banking responses, and the establishment of a clear liability mechanism for damages resulting from the operational negligence of Electronic System Providers (PSE).